Atomic Physics Studies at the Gamma Factory at CERN. Issue 8 (9th July 2020) - Budker, Dmitry; Crespo López‐Urrutia, José R.; Derevianko, Andrei; Flambaum, Victor V.; Krasny, Mieczyslaw Witold; Petrenko, Alexey; Pustelny, Szymon; Surzhykov, Andrey; Yerokhin, Vladimir A.; Zolotorev, Max
Abstract: The Gamma Factory initiative proposes to develop novel research tools at CERN by producing, accelerating, and storing highly relativistic, partially stripped ion beams in the SPS and LHC storage rings. By exciting the electronic degrees of freedom of the stored ions with lasers, high‐energy narrow‐band photon beams will be produced by properly collimating the secondary radiation that is peaked in the direction of ions' propagation. Their intensities, up to 10 17 photons per second, will be several orders of magnitude higher than those of the presently operating light sources in the particularly interesting γ–ray energy domain reaching up to 400 MeV. This article reviews opportunities that may be afforded by utilizing the primary beams for spectroscopy of partially stripped ions circulating in the storage ring, as well as the atomic‐physics opportunities made possible by the use of the secondary high‐energy photon beams. The Gamma Factory will enable ground‐breaking experiments in spectroscopy and novel ways of testing fundamental symmetries of nature. Abstract : The Gamma Factory is a new concept for producing, storing, and employing highly relativistic, partially stripped ion beams in the CERN accelerator complex. The present paper reviews research opportunities in atomic physics and related fields that open up with the advent of this radically novel experimental tool.